Role of tissue polypeptide specific antigen in the detection of prostate cancer - Onur, R; Orhan, I; Ilhan, N; Semercioz, A (Karger, 2002)
Objective: The aim of the present study was to evaluate the role of tissue polypeptide specific antigen (TPS) in the diagnosis of different stages of prostatic cancer (CaP) and to compare the diagnostic efficacy of serum TPS in respect to total prostate-specific antigen (tPSA) and free/total (f/t) PSA ratio. Patients and Methods: Patients with BPH (n=58), localized CaP (n=37) and metastatic CaP (n=16) were compared by measuring serum TPS, tPSA and f/t PSA ratio. Results: Serum TPS was significantly increased only in patients with metastatic CaP (p<0.05) and TPS levels was not significantly different between patients with BPH and localized CaP. Both f/tPSA and tPSA showed better sensitivity, specificity and receiver operating curve analysis in the differential diagnosis of BPH and localized CaP. Conclusion: In conclusion, serum TPS measurement was found to be significantly increased in metastatic prostatic carcinoma cases but was not useful in the early detection of prostatic carcinoma. Although there are several studies demonstrating the usefulness of TPS in the differential diagnosis of prostate cancer, there is increasing evidence for the use of this molecule in the late period of the disease or as an adjunct to other molecules in the detection of recurrences. Copyright (C) 2002 S. Karger AG, Basel.
Keywords: tissue polypepticle specific antigen; prostate cancer; metastatic; prostate-specific antigen